Ficus carica L. and Prunus spinosa L. extracts as new anthocyanin-based food colorants: a thorough study in confectionery products - Backes, Emanueli (2018)
The present work describes the evaluation of fig peels and blackthorn fruit extracts as natural purple colorants in doughnuts (icing) and in a typical Brazilian pastry called “beijinho”. The extracts were screened for their antioxidant activity as well as their antibacterial capacity. Nutritionally, the employed extracts did not induce significant changes, contrarily to the observed for the rheological features, mainly the darker purple tone observed when blackthorn extract was used in the icing solution. After 24 h, both prepared formulations showed a decrease in color intensity, with no significant differences between fig and blackthorn extracts. In turn, the firmness and consistency of the doughnuts benefited from using natural colorants in the icing solution, while “beijinhos” became softer and chewier, which are valued attributes. A significant increase in the antioxidant and antimicrobial activities was also observed for both natural extracts. Accordingly, the evaluated extracts are promising candidates as natural food colorants.